Gallstone pancreatitis vs alcohol-induced pancreatitis: does aetiology affect the extent of pancreatic necrosis? - Di Mauro, Davide; Alexiadis, Aris; Njere, Ikechukwu; Shams, Ola; Reece-Smith, Alex; Wajed, Shahjehan; Osman, Nermin Ahmed; Manzelli, Antonio (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The impact of different aetiologies of acute pancreatitis on the development of pancreatic necrosis (PN) is unclear. This study assessed the extent and progression of pancreatic and peripancreatic necrosis on the computed tomography (CT) scan of patients with gallstone (GP) and alcohol-induced (AIP) pancreatitis and evaluated their impact on disease severity. Methods: Patients ≥ 18-year-old with GP, AIP and PN on CT (January 2010 – September 2018), were considered. The radiological extent of PN and clinical outcomes were analysed with a logistic regression model. Results: Eighty-one patients, 59 with GP, 22 with AIP, were included. GP had a larger extent of PN when the body and/or tail of the pancreas were involved (P = 0.009). Gallstone disease (P = 0.028) and higher American Society of Anesthetists scores (P = 0.043) were predictors of necrosis diffuse to different areas of the pancreas. Predictors of single/multiple organ failure were GP (P = 0.040), necrosis > 50% of the pancreas (P = 0.002) with a diffuse pattern (P = 0.004). Conclusions: Patients with GP had a wider extent of necrosis in the pancreatic body and/or tail. The onset of organ failure can be predicted in subjects with GP and larger amount of PN.